The Impact of ASYCUDA System Implementation on the Performance of the Sudanese Customs Authority: An Evaluation Study - A. Eldaim, Akram (Journal of Commerce and Trade, 2022)
The implementation of ASYCUDA system (Automated System for Customs Data) is a critical step towards improving the performance of customs authorities in many countries, including Sudan. The system is designed to streamline processes, enhance efficiency and effectiveness, and reduce the likelihood of errors in data management. This study examines the impact of the ASYCUDA system on the performance of the Sudanese Customs Authority. A quantitative research design was used, and data were collected through a questionnaire from 24 customs officials. Descriptive and inferential statistics, including chi-square and paired samples t-test, were used to analyze the data. The results suggest that the ASYCUDA system has positively influenced the performance of the Sudanese Customs Authority, and customs officials are satisfied with its implementation. The study concludes that the ASYCUDA system can enhance the efficiency and effectiveness of the Sudanese Customs Authority and has important implications for policymakers and practitioners in the field of customs management. It is recommended that the Sudanese Customs Authority continue to use and improve the ASYCUDA system. Moreover, the authority could consider providing more training and support to ensure that all employees can effectively use the system. Classification-JEL : F14, F18, P33